2021
DOI: 10.3389/fpsyg.2021.585849
|View full text |Cite
|
Sign up to set email alerts
|

When Does Educational Level Diversity Foster Team Creativity? Exploring the Moderating Roles of Task and Personnel Variability

Abstract: This study explores how the variability of the work environment shapes the impact of educational level diversity on team creativity. By adopting an integrative framework—“status characteristics–information elaboration” model as a theoretical lens, we propose and examine the moderating roles of task and personnel variability in educational level diversity–team creativity relationship. Utilizing multiple survey data collected from 90 knowledge work teams, the empirical results indicate that educational level div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Finally, our study explores the diversity-creativity link in entrepreneurial teams with a field nested dataset from venture teams, especially in the domain of high-tech industries in China. Thus, our findings provide some of the first empirical evidence to examine how knowledge-based diversity of entrepreneurial teams facilitates TC potential, given that the prior studies on diversity-creativity relationships have been most concerned with working teams, R&D teams, and TMTs (e.g., Shin and Zhou, 2007;Buyl et al, 2011;Wang et al, 2016;Park et al, 2018;Sung and Choi, 2019;Guo et al, 2021).…”
Section: Research Implicationsmentioning
confidence: 77%
See 1 more Smart Citation
“…Finally, our study explores the diversity-creativity link in entrepreneurial teams with a field nested dataset from venture teams, especially in the domain of high-tech industries in China. Thus, our findings provide some of the first empirical evidence to examine how knowledge-based diversity of entrepreneurial teams facilitates TC potential, given that the prior studies on diversity-creativity relationships have been most concerned with working teams, R&D teams, and TMTs (e.g., Shin and Zhou, 2007;Buyl et al, 2011;Wang et al, 2016;Park et al, 2018;Sung and Choi, 2019;Guo et al, 2021).…”
Section: Research Implicationsmentioning
confidence: 77%
“…Notwithstanding the significance of exploring the effect of knowledge-based diversity on collective-level creativity (e.g., team-level creativity), few current studies have applied a multilevel approach to take the levels at which model constructs are measured into account. Specifically, although various mediating mechanisms have been involved in exploring the diversity–creativity link by prior studies, there are some flaws in that these studies have been mostly conducted only at the single-level or same-level analysis and assessment [e.g., educational specialization heterogeneity → TC at the team level, Shin and Zhou ( 2007 ); team knowledge diversity → TC at the team level, Park et al ( 2018 ); team diversity → creativity of work teams at the team level, Sung and Choi ( 2019 ); or educational level diversity → TC at the team level, Guo et al ( 2021 )]. In this respect, a small body of prior studies have applied the multilevel approach to analyze the effect of team-level knowledge-based diversity on individual-level KS and TMC, which in turn fosters team-level creativity.…”
Section: Introductionmentioning
confidence: 99%
“…, 2016). Specifically, on the other hand, educational separation diversity provokes team separation and interpersonal conflicts, which lowers team creativity and performance (Guo et al. , 2021).…”
Section: Overview Of Job-related Diversity Dimensionsmentioning
confidence: 99%
“…Thus, a team composed of people with diverse educational backgrounds can understand a problem based on various combinations of information, insights, and perspectives [38]. Studies have shown that diverse educational backgrounds may affect work outcomes and team behaviour in several aspects, such as team creativity, team performance, and innovation [21,30,40,43]. However, high educational background levels can lead to an excessive conflict of ideas that is time-consuming due to the need for reconciling knowledge, experiences, and different views [38].…”
Section: Diversity In Educational and Occupational Backgroundsmentioning
confidence: 99%
“…According to Kearney and Gebert, the formation of a team with diverse functional and educational profiles is a way to promote the integration of crossed ideas and to present to the team new perspectives and insights to solve a problem or execute a task [32]. Results of a study conducted by Guo et al have demonstrated that educational diversity may negatively affect team creativity, especially when tasks are repetitive, defined, and predictable, and personnel team variability is higher [10,21]. Cases of research have also shown that educational diversity influences, at different levels, team performance in the banking and financial sectors [45].…”
Section: Diversity In Educational and Occupational Backgroundsmentioning
confidence: 99%